APPLICATION OF DIGITAL TECHNOLOGIES FOR COMPLETE DENTURES - Yordanka Donkova; Desislava Konstantinova; Delyan Georgiev (Peytchinski Publishing, 2023)
Introduction: The daily practice shows that the patients prefer treatments that require fewer visits and low cost. The technology of conventional complete dentures follows several subsequent stages - clinical and laboratory. The search for alternative methods has led to the more and more successful development of digital technologies that could also be used for complete dentures. The conclusions of their use include higher quality, simplification of the laboratory technologies, and creation of functionally fit prosthetic structures. Purpose: The purpose of this research is to systematically review the up-to-date information available in the scientific databases in regard to the implementation of CAD/CAM technologies for the complete prosthesis. Materials and methods: A search was carried out in the period from January 2022 to October 2022 in the electronic databases PubMed, Google Scholar and ScienceDirect, using the following keywords: CAD/CAM, digital prosthesis, complete dentures, planning of complete dentures, edentulous patients, in English, German, Turkish and Bulgarian language. Conclusion: The individual anatomic and morphological particularities, age and functional changes occurring after the complete loss of teeth create conditions for the prosthesis that cannot be unified according to the scientific literature. Most probably, this is the reason why there is no straight protocol and straight technology for producing complete dentures using the digital method.